A rationally designed CD19 monoclonal antibody-triptolide conjugate for the treatment of systemic lupus erythematosus - Lai Wang; Haoyuan Yin; Jiao Jiang; Qilin Li; Changxing Gao; Wenrui Li; Bo Zhang; Yue Xin; Hongyang Li; Ming Zhao; Qianjin Lu (Elsevier, 2024)
Tripterygium wilfordii Hook F (TWHF) is a traditional Chinese medicine widely used in the treatment of systemic lupus erythematosus (SLE), with triptolide (TP) as its main active ingredient. However, its side effects also induced by TP, especially hepatotoxicity and reproductive toxicity, largely limit its application in a subset of patients. Monoclonal antibodies (mAbs) developed for the treatment of SLE that deplete B cells by targeting B cell-expressing antigens, such as CD19, have failed in clinical trials, partly due to their poor efficacy in consuming B cells. Here, we report the development of a rationally designed antibody‒drug conjugate (ADC), CD19 mAb-TP conjugate, to alleviate the side effects of TWHF and simultaneously improve the therapeutic efficacy of CD19 mAb. The CD19 mAb-TP conjugate, which was named ADC-TP, selectively depleted B cell subsets both in vitro and in vivo and effectively alleviated disease symptoms in mouse lupus models with enhanced therapeutic efficacy than CD19 mAb and fewer side effects than TP. Our present study proposes a CD19 mAb‒TP conjugate strategy to mitigate the toxicity of TWHF while also enhancing the therapeutical efficacy of CD19 mAbs for the treatment of SLE, providing a feasible method for improving the current agents used for treating SLE.